The Impact of Management, Organizing and Management of Education Financing in the Education System - Dahliar T; Kemas Imron Rosadi (Dinasti International Journal of Management Science, 2023)
This article on Literature Review of the Effects of Management, Organizing and Funding Management on the Education System is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of the Science of Education Systems in Islamic Education Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Management influences the education system; 2) Organizing affects the education system; and 3) Funding Management affects the Education System. Apart from these 3 exogenous variables that influence the endogenous variables of the Education System there are many other factors including environmental variables, community, organizational culture, commitment and creativity.